Heart xenotransplantation. Issue 6 (December 2017) - Chan, Joshua L.; Mohiuddin, Muhammad M.
Abstract : Purpose of review: Cardiac xenotransplantation has entered an exciting era, marked by numerous considerable advances in the field, and continues to be of great interest because of its potential ability in ameliorating the current constraints of limited allograft availability. This review aims to examine recent progress in this rapidly changing discipline. Recent findings: Although several hurdles remain, the use of rapidly evolving transgenic technology, in combination with novel immunosuppression regimens, has the potential to address current allogenic donor pool constraints and mechanical circulatory system device limitations. Furthermore, innovative uses of biomarker tools, such as miRNA, serve as a method for improved monitoring of xenograft status. These tools may allow for more targeted immunosuppressive strategies as well as earlier interventions to mitigate xenograft rejection. Finally, coinciding with these remarkable advances, preliminary consideration of the clinical application for cardiac xenotransplantation has begun, particularly regarding specific patient criteria for these initial clinical trials. Summary: The studies in this review highlight efforts in multiple disciplines to optimize perioperative and postxenotransplant outcomes. In examining these individual topics, this article reflects the exciting and ongoing progress in the field of cardiac xenotransplantation.